Concurrent multiple brain tuberculomas with miliary tuberculosis - A rare presentation - Kundu, Susmita; Dhua, Aparup; Ghosh, Saswata; Agarwal, Rajesh (Asian Journal of Medical Sciences, 2014)
A 45 year old immunocompetent female presented to us with fever, dry cough, vomitingand headache. There was a single episode of convulsion after hospital admission. ChestXray was normal. After through clinical examination and relevant investigations we came toknow that it was a case of concurrent multiple brain tuberculomas with miliary tuberculosis.Patient was managed with antitubercular drugs and other supportive therapy promptly and sheresponed well. Occurence of tuberculoma in the brain in a patient with miliary tuberculosisis a rare phenomenon. DOI: http://dx.doi.org/10.3126/ajms.v6i2.10279 Asian Journal of Medical Sciences Vol.6(2) 2015 118-120